Advances in miniaturized liquid sample preparation techniques for environmental analysis: A special look towards green solvents and automation - Rafael Oliveira Martins; Camila Will; Maria Flávia Assunção Magalhães; Fernando Mauro Lanças (Journal of Chromatography Open, 2025)
The continuous advancements in agricultural and industrial practices have led to the widespread introduction of various chemicals across key production sectors. While these substances offer significant benefits, their improper disposal has led to their accumulation in environmental compartments, raising global concerns about their potential impacts on ecosystems and human health. In quantitative and qualitative analysis, liquid miniaturized techniques have been widely applied to these matrices to ensure the detection and quantification of these compounds in environmental samples. Many of their advantages are rooted in key principles of green analytical chemistry, such as reduced sample and solvent consumption, as well as their versatility in enabling diverse extraction designs. However, the use of conventional organic solvents and labor-intensive extraction procedures still limits the full potential of these techniques in environmental applications. Hence, the present review provides an overview of current applications of miniaturized liquid-phase extraction protocols in environmental analysis, highlighting innovative approaches. Moreover, we discuss the use of green solvents and the potential for automation in these methods. Through this review, we aim to encourage researchers to adopt miniaturized liquid techniques for environmental monitoring, thereby advancing the implementation of more sustainable and efficient analytical strategies.